Increased Depth of Cellular Imaging in the Intact Lung Using Far-Red and Near-Infrared Fluorescent Probes - Abu-Bakr Al-Mehdi; Mita Patel; Abu Haroon; Darla Reed; B. Ohlsson-Wilhelm; K. Muirhead; Brian D. Gray (International Journal of Biomedical Imaging)
Scattering of shorter-wavelength visible light limits the fluorescence imaging depth of thick specimens such as whole organs. In this study, we report the use of four newly synthesized near-infrared and far-red fluorescence probes (excitation/emission, in nm: 644/670; 683/707; 786/814; 824/834) to image tumor cells in the subpleural vasculature of the intact rat lungs. Transpelural imaging of tumor cells labeled with long-wavelength probes and expressing green fluorescent protein (GFP; excitation/emission 488/507 nm) was done in the intact rat lung after perfusate administration or intravenous injection. Our results show that the average optimum imaging depth for the long-wavelength probes is higher (27.8±0.7 μm) than for GFP (20±0.5 μm; p=0.008; n=50), corresponding to a 40% increase in the volume of tissue accessible for high-resolution imaging. The maximum depth of cell visualization was significantly improved with the novel dyes (36.4±1 μm from the pleural surface) compared with GFP (30.1±0.5 μm; p=0.01; n=50). Stable binding of the long-wavelength vital dyes to the plasma membrane also permitted in vivo tracking of injected tumor cells in the pulmonary vasculature. These probes offer a significant improvement in the imaging quality of in situ biological processes in the deeper regions of intact lungs.